THE EFFECT OF FEE-BASED INCOME, THIRD PARTY FUNDS, AND PROFIT SHARING RATES ON THE NET PROFIT OF ISLAMIC BANKS FOR THE 2016-2020 PERIOD - Indah Muflikhah; Fil Isnaeni (Transpublika Publisher, 2022)
The purpose of this study is to determine the effect of Fee Based Income, Third Party Funds, and Profit Sharing Rates on Net Profit in Islamic Commercial Banks with the research period from 2016-2020. This study used quantitative methods, while the type of data used is secondary data. The populations in Islamic Commercial Banks with the research period from 2016-2020. The number of samples used in this study were 6 Bank determined by using purposive sampling method based on predetermined criteria. The result revealed that Fee Based Income insignificant effect on Net Profit, Third Party Funds significant effect on Net Profit, and Profit Sharing Rates insignificant effect on Net Profit. Simultaneously Fee Based Income, Third Party Funds, and Profit Sharing Rates significant effect on Net Profit in Islamic Commercial Banks with the research period from 2016-2020. The R-Squared result is 0.315090 or 0.31% the dependent variable is influenced by the independent variable in the model. Meanwhile, the remaining 69% is influenced by other variables outside the model such as Non Performing Financing, Financing to Deposit Ratio, Inflation, BI 7-Day Reserve Repo Rate, Inflation Rate, Own Capital, and Lease Financing.